Kenaf Seed Supercritical Fluid Extract Reduces Aberrant Crypt Foci Formation In Azoxymethane-induced Rats. - Siti Aisyah Abd Ghafar; Latifah Saiful Yazan; Paridah Md Tahir; Maznah Ismail (Elsevier, 2024)
Kenaf (Hibiscus cannabinus) a plant of the family Malvaceae, is a valuable fiber plant native to India and Africa. Kenaf seeds contain alpha-linolenic acid, phytosterol such as β-sitosterol, vitamin E and other antioxidants with chemopreventive properties. In the present study we examined the hypothesis that kenaf seed ‘supercritical fluid extract’ (SFE) extract could suppress the early colon carcinogenesis in vivo by virtue of its bioactive compounds. To accomplish this goal, 60 male rats were randomly assigned to 5 groups which were (1) negative control group [not induced with azoxymethane (AOM)]; (2) positive control group (induced with AOM but received no treatment); (3) group treated with 500 mg/kg kenaf seed SFE extract; (4) group treated with 1000 mg/kg kenaf seed SFE extract; (5) group treated with 1500 mg/kg kenaf seed SFE extract. At 7 weeks of age, all rats except the negative control group received 15 mg/kg of AOM injection subcutaneously once a week for 2 weeks. Rats were euthanized at 13 weeks of the experiment. Number of ACF (mean ± SD) ranged from 84.4 ± 4.43 to 179.5 ± 12.78 in group 2, 3, 4, 5. ACF reductions compared with the untreated group were 45.3, 51.4 and 53.1% in rats fed with 500, 1000 and 1500 mg/kg body weight, respectively. There were no significant differences in weight gain among groups. Our finding indicates that kenaf seed SFE extract reduced AOM-induced ACF in Sprague–Dawley male rats.